A Comparison of the Effects of Rhizophagus Intraradices, Serendipita Indica, and Pseudomonas Fluorescens on Soil and Zea Maize L. Properties under Drought Stress Condition - Pourraeisi, Arman; Boorboori, Mohammad Reza; Sepehri, Mozhgan (International Journal of Sustainable Agricultural Research, 2022)
Drought is one of the most critical environmental stresses that reduce agricultural production. This study aimed to examine the effects of individual and simultaneous inoculation of Rhizophagus intraradices, Serendipita indica, and Pseudomonas fluorescens on the physical properties of soil and the growth parameters of single cross 704 maize under three levels of drought stress (80%, 50%, and 25% available water). It was found that Rhizophagus intraradices significantly increased soil hydrophobicity at all levels of drought stress, as did Serendipita indica at the second and third levels. Pseudomonas fluorescens, on the other hand, decreased soil hydrophobicity at all drought levels. At the optimum moisture level, individual inoculations of the investigated microorganisms did not significantly affect mean weight diameter, but all studied microorganisms increased mean weight diameter as drought stress increased. Additionally, inoculating plants with Rhizophagus intraradices at all levels of drought stress significantly increased the dry and fresh weight of shoots. Nevertheless, inoculating plants with Rhizophagus intraradices and Pseudomonas fluorescens at all levels of drought stress led to a significant increase in plant shoot height. Plant shoot potassium concentrations were significantly reduced by individual inoculation of Pseudomonas fluorescens and Serendipita indica under drought stress at the first and third levels. However, at all drought stress levels, inoculating plants with Rhizophagus intraradices significantly increased phosphorus concentrations in the shoots. Based on the results of this study, simultaneous insemination of maize with Rhizophagus intraradices and Serendipita indica was the most effective microorganism treatment for reducing the harmful effects of drought stress and improving soil properties.